Study of Electromagnetic Properties of Field-Effect Transistors (FET) in Integrated Circuits - Ghofrane Boulebda (My University, 2026)
The latest innovations in integrated circuits have revolutionized the world of electronics.Today the industry no longer aims merely to miniaturize while satisfying a physical equation in order to achieve superior performance. The most important component in this process is the transistor. To achieve optimal performance,we have used the WCIP iterative method in this work,which is based on a wave-function model the MATLAB environment. We were able to study the energy yield of the three most recently used structures: FinFET, Nanowire, SB-CNTFET. --------------------------------------------------------------------- أحدث الدوائر المتكاملة ثورة في عالم الألكترونات حيث اصبح العالم اليوم لا يهدف فقط لتصغير بل اصبح يهدف الى التصغير مع تحقيق معادلة فيزيائية من اجل الحصول على اداء فائق واهم عنصر فيها هو ترانزيستور ولتحقيق الاداء المثالي قمنا في هذا العمل بدراسة بمحاكاة من خلال الطريقة التكرارية ((WCIP التي تعتمد على مفهوم الموجة بالاستعانة ببيئةMATLAB تمكنا من دراسة المردود الطاقوي لأحدث هياكل استخداما في الآونة الأخيرة (FinFET,Nanowire ,SB-CNTFET). -------------------------------------------------------------------- Les dernières innovations en matière de circuits intégrés ont révolutionné le monde de l'électronique. Aujour'hui,l'objectif n'est plus seulement la miniaturisation associée à la réalisation d'une équation physique afin d'obtenir des performances supérieures,dont l'élément clé est le transistor. Afin d'atteindre des performances optimales,nous avons dans le cadre de ce travail,réalisé une simulation à l'aide de la méthode itérative WCIP qui s'appuie sur un de l'onde de hom à l'aide de l'environnement MATLAB. Nous avons ainsi pu étudier le rendement énergétique des trois derniéres structures utilisées récenmment: FinFET, Nanowire, SB-CNTFET.
Keywords: : Transistor-field effect transistor-Integrated circuits-Electromagneticcharacteristics-Wave Concept Iterative WCIP-MATLAB environment -energy efficiency; ترونزيستور- ترونزيستور الاثر الحلقي-دوائر المتكاملة- خصائص كهرومغناطسية-طريقة التكرارية -WCIP بيئة ماتلاب-مردود طاقوي¬¬; Transistor -Transistor à effet de champ - circuits intégrés – Caractéristiques électromagnétiques-Méthode itérative WCIP-Environnement MATLAB-rendement énergétique